Fixed Yet Flexible: Non-Rigid Connector Strategy for Pier Abutments – A Case Report - Biswas, Dr. Swarnali (International Journal Of Drug Research And Dental Science, 2025)
Introduction: Pier abutments, located between two edentulous spaces, pose unique biomechanical challenges in fixed prosthodontics. Conventional fixed partial dentures (FPDs) with rigid connectors are often unsuccessful in such cases due to the fulcrum effect, which can lead to prosthesis failure. Non-rigid connectors are a proven solution that allows limited movement within the prosthesis, reducing stress on abutment teeth.Case Presentation: This case report presents a 29-year-old male patient with missing right maxillary canine and second premolar. The first premolar served as a pier abutment between the edentulous spaces. Clinical and radiographic evaluations confirmed the abutments were periodontally sound. A new prosthetic plan was executed using a porcelain-fused-to-metal FPD incorporating a non-rigid key-keyway connector. The key (male) was placed on the distal surface of the pier abutment, and the keyway (female) on the mesial surface of the pontic replacing the second premolar.Conclusion: Non-rigid connectors are essential in managing pier abutment cases to reduce stress and enhance prosthetic longevity. This case reinforces the value of biomechanically sound prosthodontic design in achieving long-term success.